Pemodelan Pengaruh Nomor dan Kecepatan Pengantar Benang Terhadap Kekuatan Benang Ring Spinning Menggunakan Mekanika Klasik dan Regresi Multivarian Nonlinear - Valentinus Galih Vidia Putra; Andrian Wijayono; Irwan Irwan; Totong Irwan; Cahaya Rosyidan (Jurnal Fisika FLUX, 2019)
The application of theoretical physics can be found in textile processing such as yarn manufacturing process. The aim of this research is to determine and to develop a new model to predict the yarn strength of ring spun yarn influenced by the yarn count number (in unit m/g) as well as the delivery speed of yarn in bobbin (vf). In this research we have found a new model to predict the yarn strength on ring spinning machine based on classical mechanics as well as statistical method using nonlinear  multivariate regression .According to this research, we have established that both classical mechanics and nonlinear  multivariate regression can be applied  and developed to predict yarn strength as a function of yarn delivery speed and yarn count number both theoretically and experimentally.